The Relationship Between Social Media Addiction And Body Dysmorphic Disorder Teenagers: Implications in Guidance and Counseling - Diah Novitrah Pangestuti; Yuda Syahputra; Smita Biju Thomas; Chiman Mohammadi Nasab (Asosiasi Asesmen Pendidikan (AAP), 2025)
The purpose of this study was to determine the relationship between social media addiction and body dysmorphic disorder in teenagers. The research method used was a quantitative approach. The population and sample in this study were adolescents aged 15–18 years in Tajurhalang, Bogor City. Data were collected using a questionnaire (Social Media Addiction Scale and Body Dysmorphic Disorder Scale) from a population of 310 people, selected using random sampling techniques and the Slovin formula, with a sample size of 225 people. Data were analyzed using SPSS software version 23. Hypothesis testing used the Pearson product-moment correlation. The results of the hypothesis test showed a significance level of 0.000 <0,05, thus rejecting H0 and accepting Ha. The correlation coefficient value of r = 0,589 indicates that the relationship between the two variables is moderate. The study concluded that there is a relationship between social media addiction and body dysmorphic disorder. These findings are beneficial for schools in designing more effective counseling programs to address social media addiction, which can lead to tendencies toward body dysmorphic disorder.